The relationships between teachers' teaching performance and levels of motivation and job-related needs satisfaction at the Perpetual Help College of Laguna, 1988-1989 - Reyes-Domingo, Susana L. (Animo Repository, 1989)
This study involved 109 faculty of the Perpetual Help College of Laguna during the school year 1988-1989. It determined the degree to which the teachers' teaching performance was related with their levels of work motivation and job-related needs satisfaction. The descriptive-correlational method of research was used in this study. Four questionnaires, the Teacher Behavior Inventory, the Work Motivation Scale, the Factors Important In My Job Questionnaire, and a Personal Information Sheet were used to gather data. Descriptive statistics such as percentages, weighted means, and standard deviations were used in presenting the teachers' profile (i.e. age, sex, marital status, educational qualification, teaching experience, level of motivation, and degree of job-related needs satisfaction). Multiple correlation and multiple regression through stepwise regression were used to determine the significant correlates and predictors of the dependent variable, teachers' teaching performance. Based on the findings of the study, the following conclusions were drawn: 1. The teachers perceived their job-related needs to be greatly satisfied by the school and that they assessed themselves to be highly motivated, so therefore, the administrators of the respondent school had a high employee-orientation or concern for their teachers. 2. The teachers' teaching performance was independent of their job-related needs satisfaction and levels of motivation, as well as the other selected variables. 3. The absence of significant relationships between teaching performance and the selected variables, led to the conclusion that there were factors other than those included in the study, which might be related with teaching performance.